Academic Dishonesty Selama Masa Pandemi Covid-19 (Studi Kasus pada Mahasiswa PTKU MUI SU) - Nikmatur Ridha; Irvan Mangunsong; Nurul Fadilah; Ani Asnita Harahap (Al-Ulum: Jurnal Pendidikan Islam, 2020)
The background to this research problem is based on the large numbenumberPTKU MUI SU students in carrying out face-to-face learning activities during the covid-19 pandemic. This research uses descriptive qualitative research which aims to obtain information directly in accordance with field facts so as to produce a research that can be scientifically justified. The results of this study are PTKU MUI SU students founded by the North Sumatra Indonesian Ulama Council (MUI SU), including students who have integrity and are free from academic dishonesty.Keywords: academic dishonesty, pandemic and student